Paragraph Development in Writing a Process Essay through LMS Forum-Based Collaborative Writing - Siti Musarokah; Issy Yuliasri; Sri Wuli Fitriati; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2023)
This study aims at investigating how the students develop the paragraphs in writing a process essay through LMS Forum-Based Collaborative Writing. This study also aims at describing the completeness of major and minor supporting sentences in the body paragraphs of the process essay developed. The design of the study is qualitative descriptive, the object of the study was the paragraphs written by the fourth semester students of the English Education Study Program of Universitas PGRI Semarang. Documentation was used to collect the data, that is in the form of paragraphs taken from LMS Forum submitted by the students in groups. The data was then analyzed by using qualitative data analysis consisting of data reduction, data display and drawing conclusion. The result of the study shows that in writing the process essay in the introduction, the students used two techniques, namely common problem and series of question; chronological order was mostly used to support the thesis statement in the body paragraphs; and in concluding paragraphs, the students conclude the essay by paraphrasing the thesis statements and summarizing the main points in the body paragraphs. Moreover, in developing the paragraphs, there are 7 paragraphs or 41,18% which reach completeness. Moreover, 8 or 47,06 % paragraphs are categorized half complete, and 2 or 11,76 paragraphs are categorized incomplete. It can be concluded that some of the students’ paragraph development do not reach completeness.